Surgery for autoimmune aortitis: unanswered questions - Amr A. Arafat (The Cardiothoracic Surgeon, 2019)
Abstract Background The aorta is rarely affected by autoimmune vasculitis, which can lead to aortic dilatation requiring surgery. Autoimmune aortitis may affect one aortic segment or the entire aorta, and in some cases, the aorta may be affected at different time intervals. Because of the rarity of the disease and the limited cases described in the literature, management of autoimmune aortitis is still controversial. We aimed to review the current literature evidence regarding these controversial aspects for the management of autoimmune aortitis and give recommendations based on this evidence. Main text Immunosuppressants are generally indicated in vasculitis to halt the progression of the disease; however, its role after the occurrence of aortic dilatation is debatable since further aortic dilatation would eventually occur because of the weakness of the arterial wall. In patients with a localized ascending aortic dilatation who required surgery, the optimal approach for the distal aorta is not known. If the probability of disease progression is high, it is not known whether the patients would benefit from postoperative immunosuppressants or further distal aortic intervention may be required. The risk of rupture of the weakened aortic wall was not established, and it is debatable at which diameter should these patients have surgery. In patients with previous ascending surgery for autoimmune aortitis, the endovascular management of the distal aortic disease has not been studied. The inflammatory process may extend to affect the aortic valve or the coronary vessels, which may require special attention during the procedure. Conclusion Patients with diagnosed autoimmune aortitis are prone to the development of the distal aortic disease, and endovascular intervention is feasible in those patients. Patients with concomitant aortic valve can be managed with the aortic valve-sparing procedure, and preoperative screening for coronary disease is recommended. Immunosuppressants should be used early before aortic dilatation, and its role postoperatively is controversial.